Knowledge and Oral Hygiene Practice by School Children in Cox’s Bazar, Bangladesh - Kabir, Mohammad Nazmul; Ahmed, Md Bashir; Khan, Mahbuba (Update Dental College Journal, 2019)
Background: A healthy mouth enables people to eat, speak and socialize without pain, discomfort or embarrassment. The Oral cavity is a portal of entry and the site for microbial infections that affect overall health status; Oral diseases are one of the most prevalent diseases, endangering our health and safety. Objectives: the objective of this study was to identify oral hygiene practiced by school children in Cox’s Bazar, Bangladesh Methods: A descriptive cross-sectional study carried out among 474 students of class IX of at randomly selected Schools in Cox’s Bazar, Bangladesh. The samples were collected by purposive sampling technique and a structured questionnaire considering objectives of the study was used to collect data, Data were collected by faceto- face interview of the students, SPSS software (version 19) was used to analyze the data, and descriptive statistics and chi-square test were done. Results: Maximum, {274(57.8%)} children brushed their teeth every day at age of 5 to 10) years, and 233 (49.2%) children Brushed their teeth at morning and night, Relationship between age and oral hygiene practice is statistically significant (P value 0.03). Male and female are relatively same in oral hygiene practice. Most of {438(92.4%)} the children clean teeth with tooth brush and tooth paste, 243(51.3%) children used tooth brush in upward and downward direction. Conclusion: Age, parents’ education, teachers, others personnel’s and media are important factors to motivate the children to maintain oral hygiene regularly, property and using teeth cleaning devices and materials. Update Dent. Coll. j: 2019; 9 (2): 27-31